Multivariate Analysis when Choosing the First Programming Language Studied in Universities - Prokop, Yuliia; Trofimenko, Elena; Loginova, Nataliia; Zadereyko, Alexander; Gerganov, Maksym; Прокоп, Юлія; Трофименко, Олена; Логінова, Наталія; Задерейко, Олександр; Герганов, Максим; Прокоп, Юлия; Трофименко, Елена; et al. (My University, 2019)
Since the key point of training IT specialists is based on the labor market demands and the compliance of the employer's requirements with the knowledge and skills of future programmers acquired during the training, the authors conducted a study of the Ukrainian IT labor market. To demonstrate the distinctive features of the domestic and foreign IT markets, a comparative rating of programming languages in the labor market in Ukraine and in other countries was made. A survey of IT students and experienced programmers was conducted as another factor of the study. Based on many years of the authors’ teaching experience and the result of analyzing the opinions of interviewed programmers, the requirements for the first programming language studied in universities by IT-students were determined. According to these requirements, a system of numerical evaluation of practical criteria for the first language programming selection among the most demanded ones was worked out. A total rating for each language was created in order to identify the most suitable programming language for teaching the beginners.

Оскільки ключовим моментом підготовки ІТ-фахівців є вимоги ринку праці та відповідність вимог роботодавця до знань та навичок майбутніх програмістів, набутих під час навчання, автори провели дослідження українського ринку праці в сфері ІТ. Для демонстрації відмінних рис вітчизняного і зарубіжного ІТ-ринків був проведений порівняльний рейтинг мов програмування на ринку праці в Україні та інших країнах. Одним із факторів дослідження є проведене опитування ІТ-студентів та досвідчених програмістів. Ґрунтуючись на багаторічному досвіді викладання і результатах аналізу думок опитаних програмістів, визначено вимоги до першої мови програмування, що вивчається в університетах IT-студентами. Відповідно до цих вимог розроблено систему чисельного оцінювання практичних критеріїв для вибору мови програмування серед найбільш затребуваних. Складено загальний рейтинг для кожної мови програмування з метою визначення найбільш придатної мови для навчання ІТ-початківців.

Поскольку ключевым моментом подготовки ИТ-специалистов являются требования рынка труда и соответствие требований работодателя знаниям и навыкам будущих программистов, приобретенным в ходе обучения, авторы провели исследование украинского рынка труда в сфере ИТ. Для демонстрации отличительных черт отечественного и зарубежного ИТ-рынков был проведен сравнительный рейтинг языков программирования на рынке труда в Украине и других странах. Опрос IT-студентов и опытных программистов был проведен в качестве еще одного фактора исследования. Основываясь на многолетнем опыте преподавания и результатах анализа мнений опрошенных программистов, были определены требования к первому языку программирования, изучаемому в университетах IT-студентами. В соответствии с этими требованиями была разработана система численной оценки практических критериев выбора языка программирования среди наиболее востребованных. Был составлен общий рейтинг для каждого языка, чтобы определить наиболее подходящий язык программирования для обучения.
Prokop Yu. Multivariate Analysis when Choosing the First Programming Language Studied in Universities / Yu. Prokop, E. Trofimenko, L. Loginova, A. Zadereyko, M. Gerganov // 2019 IEEE 2nd Ukraine Conference on Electriсal and Computer Engineering (UKRCON). - Lviv : 2019. - P. 1224-1228.
Keywords: programming language; introductory course; IT labor market; teaching programming; basics of programming; мова програмування; вступний курс; ІТ-ринок праці; навчання програмуванню; основи програмування; язык программирования; вводный курс; ИТ-рынок труда; обучение программированию; основы программирования